2020
DOI: 10.1177/2333393620972958
|View full text |Cite
|
Sign up to set email alerts
|

“My Color Doesn’t Lie”: Race, Gender, and Nativism among Nurses in the Netherlands

Abstract: Nursing in white-majority populations tends to be associated with white women. Yet as Western Europe and North America undergo demographic shifts, such associations are challenged as people of different racial and national backgrounds take on positions in nursing and other professional roles in healthcare. This article explores the work experiences of nurses from diverse backgrounds as they confront intersecting forms of sexism, racism, and nativism in the Netherlands. We use the conceptual framework of “appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…For MNs of color, it became clear that racism ensured that they would never be accepted. The pervasiveness of racism toward MNs of color has been noted in many other studies across the globe (Alexis, 2015; Balante et al, 2021; Buttigieg et al, 2018; Cottingham & Andringa, 2020; Dahl et al, 2017; Lin et al, 2018; Roth et al, 2021; Smith et al, 2022) and was identified as interfering with acculturation in our qualitative interviews. MNs reported racism at work in their roles as healthcare professionals and while undergoing treatment in their roles as consumers of healthcare.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…For MNs of color, it became clear that racism ensured that they would never be accepted. The pervasiveness of racism toward MNs of color has been noted in many other studies across the globe (Alexis, 2015; Balante et al, 2021; Buttigieg et al, 2018; Cottingham & Andringa, 2020; Dahl et al, 2017; Lin et al, 2018; Roth et al, 2021; Smith et al, 2022) and was identified as interfering with acculturation in our qualitative interviews. MNs reported racism at work in their roles as healthcare professionals and while undergoing treatment in their roles as consumers of healthcare.…”
Section: Discussionsupporting
confidence: 69%
“…MNs who are culturally and linguistically diverse from the native population are at particular risk for these stresses and difficulties (Schilgen et al, 2019). Unequal wages, unfair promotion practices, racism, and discrimination have been reported by MNs from Australia (Smith et al, 2022), Germany (Roth et al, 2021), the Netherlands (Cottingham & Andringa, 2020), the United Kingdom (Lin et al, 2018), the United States (Connor, 2016), and several other countries (Balante et al, 2021). MNs, therefore, have health risks due to psychological and social stresses (Goh & Lopez, 2016; Pung & Goh, 2017).…”
Section: Introductionmentioning
confidence: 99%